An analysis of cultural diversity in spanish educational legislation: a historical overview - Peñalva Vélez, Alicia (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
In this paper we analyze the Educational Laws approved in Spain since 1990, with the aim of identifying any references about cultural diversity. All these laws have come into force within a new multicultural Spanish reality, which has already been existing in other European countries for decades. However, the Spanish legal system (including educational law) still focuses on cultural differences of those migrants that are non EU members. Our Social Imaginary is composed of distorted images of what cultural diversity is, and what it means. We should introduce intercultural educational model at schools, as interculturality pursues the renovation of monocultural scholar curricula. Its objective is to promote the diverse cultural groups at schools, apart from trying to achieve cultural feedback within society. The most important problem we have currently faced in the educational system is that cultures, far from being clearly defined as global, dynamic and open, are being constrained to ethnic, geographical or religious features